Scientific tourism an alternative to conserve CIPCA Heritage, Amazonia - Ecuador - Silva, Paola (2019)
The research focused on the identificaction of natural and cultural heritage with scientific potential in Centrode Investigación Posgrado y Conservación Amazónica (CIPCA), in the selection of places with scientific potential and in the analysis of the criteria that affect their potential. The purpose is to link tourism with science, in a way that fosters a scientific culture, ideal for fragile and environmental friendly territories.  In this way insert CIPCA into the tourist activity focused on the discovery of its heritage. This is consisting of socio-environmental units attached to research projects. The research was developed at CIPCA-UEA. The identification of heritage was carried out based on the methodology: MINTUR (2017a), which establishes a hierarchy of tourist attractions based on the conditions they present. The selections of the attractions with scientific potential, were developed through the criteria of experts and Delphi method. The analysis of the incidence of the criteria with the attractions’ scientific potential was performed with Descriptive Statistics, Contingency tables and Chi-square test. The results were: 14 cultural and 2 natural attractions, 16 tourist attractions, of which 2 attractions respond to hierarchy II and 14 to hierarchy I. Through the assessment it was established that CIPCA has 9 cultural attractions with a medium level of scientific potential. These results expose the need to strengthen the criteria with a high incidence in determining the scientific potential of the attractions, which are: pedagogical value, scientific production, human resources,infrastructure and technological equipment.